A naturalistic examination of social comparisons and disordered eating thoughts, urges, and behaviors in college women. Issue 2 (26th November 2015) - Fitzsimmons‐Craft, Ellen E.; Ciao, Anna C.; Accurso, Erin C.
ABSTRACT: Objective: We examined the effects of body, eating, and exercise social comparisons on prospective disordered eating thoughts and urges (i.e., restriction thoughts, exercise thoughts, vomiting thoughts, binge eating urges) and behaviors (i.e., restriction attempts, exercising for weight/shape reasons, vomiting, binge eating) among college women using ecological momentary assessment (EMA). Method: Participants were 232 college women who completed a 2‐week EMA protocol, in which they used their personal electronic devices to answer questions three times per day. Generalized estimating equation models were used to assess body, eating, and exercise comparisons as predictors of disordered eating thoughts, urges, and behaviors at the next report, adjusting for body dissatisfaction, negative affect, and the disordered eating thought/urge/behavior at the prior report, as well as body mass index. Results: Body comparisons prospectively predicted more intense levels of certain disordered eating thoughts (i.e., thoughts about restriction and exercise). Eating comparisons prospectively predicted an increased likelihood of subsequent engagement in all disordered eating behaviors examined except vomiting. Exercise comparisons prospectively predicted less‐intense thoughts about exercise and an increased likelihood of subsequent vomiting. Discussion: Social comparisons are associated with later disordered eating thoughts and behaviors in the natural environment and may need to be specifically targeted in eating disorder prevention and intervention efforts. Targeting body comparisons may be helpful in terms of reducing disordered eating thoughts, but eating and exercise comparisons are also important and may need to be addressed in order to decrease engagement in actual disordered eating behaviors. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:143‐152).